ASPEK IMUNOLOGI SLE - -, Yuriawantini; Suryana, Ketut (journal of internal medicine, 2007)
Systemic Lupus Erythematosus (SLE) is autoimmune disease characterised by the production ofautoantibodies to component of the cell nucleus in association with a diverse array of clinical manifestations.The patho-aetiology of systemic Lupus Erythematosus probably involves multifactorial interaction amongvarious genetic and environmental factors. Multiple genes contribute to disease susceptibility, including genesencoding complement and other components of the immune response. The interaction of sex, hormonal millieuand the hypothalamus-pituitary-adrenal axis modifies this susceptibility and the clinical expression of thedisease. Defective immune regulatory mechanism, such as the clearance of apoptotic cells and immunecomplexes, are important contributors to the development of SLE. The loss of immune tolerance, increaseantigenic load, excess T cells helper, defective B cell suppression, and the shifting of T helper 1 (Th1) to Th2immune responses leads to the B cell hyperactivity and the production of pathogenic autoantibodies. ANAs areantibodies against both functional and structural in the cell nucleus. ANA is early detection of autoantibodies forthe patient with clinical features that suggest SLE. Positive test for antinuclear antibodies may support thediagnosis, especially if more spesific autoantibodies are present, such as anti-double-stranded DNA, anti-Sm,anti-RNP or anti-Ro. Understanding the value of autoantibody testing in patient care requires clinical judgmentand experience.